Radiation exposure of Staff handling 18Fluorine-Fluorodeoxyglucose in a new positron emission tomography/computed tomography centre - Lerato Mosima; Nathaniel Muzamhindo; Maryke Lundie; Beverley Summers (AOSIS, 2023)
Background: Positron emission tomography/computed tomography (PET/CT) is an imaging modality that combines images from high-energy gamma rays emitted by a positron emitting radiopharmaceutical and those from the CT component. The images are then used in the diagnosis of severe diseases. Procedures with PET radiopharmaceuticals introduce a risk of high occupational radiation exposure to staff handling them. 18Fluorine-Fluorodeoxyglucose ([18F]FDG) is the most commonly used PET radiopharmaceutical. Aim: To determine the radiation exposure of staff working at the PET/CT facility. Setting: Academic hospital in Gauteng. Methods: The study was quantitative and descriptive. The radiation exposure data of participants were collected using Polimaster®electronic pocket dosimeters, ring dosimeters and thermoluminescent dosimeters. The participants' workflow was tracked and the tasks that led to the highest radiation exposure were identified. Results: Radiopharmacists had 129 dispensing days with the resultant daily radiation exposure ranging between 0.01 µSv and 0.32 µSv. The radiographers' daily radiation exposure ranged between 7.08 µSv and 19.14 µSv. Radiographers received the highest radiation dose during radiopharmaceutical injection (average = 1.86 µSv). Conclusion: The study found that staff working at a new PET/CT facility in Gauteng were not at risk of radiation exposure above the accepted annual limits, which are 20 mSv per annum, averaged over 5 years, and with no more than 50 mSv in 1 year. Contribution: The findings revealed the need for continuous training in radiation protection measures for all staff working in the PET/CT facility.